2013
DOI: 10.1007/s00122-013-2221-7
|View full text |Cite
|
Sign up to set email alerts
|

Golden SusPtrit: a genetically well transformable barley line for studies on the resistance to rust fungi

Abstract: Therefore, a doubled haploid (DH) mapping population (n = 122) was created by crossing SusPtrit with Golden Promise to develop a 'Golden SusPtrit', i.e., a barley line combining SusPtrit's high susceptibility to non-adapted rust fungi with the high amenability of Golden Promise for transformation. We identified nine genomic regions occupied by resistance quantitative trait loci (QTls) against four non-adapted rust fungi and P. hordei isolate 1.2.1 (Ph.1.2.1). Four DHs were selected for an Agrobacterium-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…suggested that a region close to TFA2 on chromosome 2H, of the line SG062N, may affect transformation efficiency. The locations of TFA6 and TFA8 also correspond with regions previously reported by Yeo et al 5. Mano et al 6,.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…suggested that a region close to TFA2 on chromosome 2H, of the line SG062N, may affect transformation efficiency. The locations of TFA6 and TFA8 also correspond with regions previously reported by Yeo et al 5. Mano et al 6,.…”
Section: Discussionsupporting
confidence: 89%
“…reported that barley cultivar ‘Lenins’ has higher regeneration ability compared to some other cultivars, but that trait alone is not enough for efficient transformation. Yeo et al 5. suggested that a region close to TFA2 on chromosome 2H, of the line SG062N, may affect transformation efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the experimental research line SusPtrit (Atienza et al 2004), which has been developed to have extraordinarily high susceptibility to heterologous rust fungi, proved to be instrumental in elucidating the inheritance of nonhost resistance. Mapping populations were developed with SusPtrit using the regular, immune, cvs Vada, Cebada Capa and Golden Promise as resistant parents (Jafary et al 2006(Jafary et al , 2008Yeo et al 2014).…”
Section: Introductionmentioning
confidence: 99%